In the Realm of Legal and Moral Philosophy : critical encounters - Kramer, Matthew H. 1959- (New York : St. Martin's Press, 1999)
In this wide-ranging investigation of many prominent issues in contemporary legal, political, and moral philosophy, Matthew Kramer combines penetrating critiques with original theorizing as he examines the writings of numerous major theorists (including Ronald Dworkin, H. L. A. Hart, Alan Gewirth, David Lyons, Ronald Coase, John Finnis, Jules Coleman, Anthony Kronman, and Richard Posner).
While Kramer argues with the rigor that is the hallmark of the tradition of analytic philosophy, his inquiries extend not only to that tradition but also to such other traditions as Aristotelianism and Continental philosophy and Legal Realism.
1. What Good is Truth? -- 2. How Not to Oppugn Consequentialism -- 3. Justice as Constancy -- 4. Questions Raised and Questions Begged: Some Doubts about Ronald Dworkin's Approach to Law-and-Economics -- 5. The Philosopher-Judge: Some Friendly Criticisms of Richard Posner's Jurisprudence -- 6. A Coda to Coase -- 7. In Praise of the Critique of the Public/Private Distinction -- 8. Of Aristotle and Ice Cream Cones: Reflections on Jules Coleman's Theory of Corrective Justice -- 9. Getting the Rabbit Out of the Hat: A Critique of Anthony Kronman's Theory of Contract -- 10. Reason without Reasons: A Critique of Alan Gewirth's Moral Philosophy.
Includes bibliographical references and index.
Keywords: Law -- Philosophy